ANALISIS PEMBIAYAAN PRODUKTIF DALAM PENGEMBANGAN USAHA MEBEL ( STUDI PADA UD. ASNUR MANDIRI JL KH AGUS SALIM BONE) - Nurul Faijah; Abd Hafid; Muh Arafah (Nurul Jadid University, 2024)
Financing allows companies to obtain financial assistance or capital to develop businesses and generate profits. This study aimed to explain the utilization of financing, particularly productive financing, in the development of the furniture business at UD Asnur Mandiri. This study used a qualitative field research approach and data collection techniques such as observation, interview, and documentation. The collected data was then analyzed comprehensively. The analysis revealed that UD Asnur Mandiri could develop its business through the use of productive financing. The indicators of business development demonstrate the utilization of financing to boost raw materials, labor, production, customer base, and revenue. Therefore, the use of financing by UD. Asnur Mandiri significantly influences its business development.